Effect of Micronutrients on The Two Qatari Date Palm Cultivars Shishi and Lulu Through in Vitro Technic - Aqeel, Sara; A. Sidky, Rehab (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Plant tissue responds to nutrient media due to the plant cultivars genetic diversity. The objective of this research is to determine the effects of micronutrients on date palm growth and which of these micronutrients are critical for improving growth combined with Paclobutrazol or without on in vitro of elongation stage. In vitro growth of two cultivars were determined by varying five treatments that included minor salts (EDTA-chelated iron, CuSo4,) alone or combined with Paclobutrazol. The effects of these five treatments on plantlet length, trunk thickness, rooting number and Chlorophyll A, B was investigated. The results obtained after three months showed that, increasing copper sulphate on MS elongation media combined with Paclobutrazol was more effective for increasing the trunk thickness as well as rooting number compared with normal MS level. While poor response was found when Fe was increased in the chelated form of Fe-EDTA on MS elongation media. For cultivars, Shishi gave the highest plantlets length as well as root number. The maximum content of chlorophylls A and B were observed when copper sulphate was increased on MS elongation media with cultivar Lulu. The survival rate after 3 months was related to the medium used during the elongation phase, the survival of plantlets reached to 98.66% with cultivar lulu at the acclimatization stage.